Row middle herbicide programs for plasticulture vegetables using targeted herbicide applications - Ana C. Buzanini; Arnold W. Schumann; Nathan S. Boyd (Weed Technology)
In plasticulture production, smart-spray technology can detect weeds and apply herbicides only where needed in the area between raised, plastic-covered beds (row middle). This technology has the potential to reduce herbicide use and lower input costs. A prototype smart-spray system was developed at the Gulf Coast Research and Education Center in Wimauma, FL, that uses YOLO-V3 convolutional neural networks to differentiate broadleaf, grass, and nutsedge weeds in row middles. Two sets of field experiments were conducted to determine the efficacy of smart-spray technology using a combination of preemergence and postemergence herbicides. Weed density was reduced after all treatments, and targeted applications were as effective as banded treatments. Overall, including a preemergence herbicide tended to lower weed density compared to postemergence herbicides alone, regardless of application technique. Two banded preemergence herbicide applications and two targeted postemergence applications reduced herbicide use by 52% and 13% compared to banded preemergence and postemergence applications in Experiments 1 and 2, respectively. The reduction from two to one preemergence herbicide application did not result in an overall reduction in herbicide use or cost in Experiment 1 because the decrease in preemergence herbicides resulted in increased postemergence herbicide usage. In the absence of a banded preemergence application, with targeted postemergence applications compared to banded applications, herbicide usage was reduced by 40% to 67% in Experiment 1 and by 79% to 84% in Experiment 2. Smart-spray technology is an effective weed management tool for row middles in plasticulture production systems with or without preemergence-herbicide applications.